Behind The Scenes Implementation of Islamic Law and Positive Law in Re-sponding To 'Sound Horeg' In Indonesia - Winanda, Pandu Arya; Alam, Syariful (IHSA Institute, 2025)
This study analyzes the implementation of Islamic law and positive law in responding to contemporary social problems, particularly regarding the proper use of sound horeg in society. The method used is empirical juridical, with the first discussion topic being the problematic of sound horeg in Indonesia, the second being the legal approach to violations of sound horeg in society, and the controversy of sound horeg as a culture in Muslim society. Primary data was obtained through interviews and direct observation, while secondary data came from laws and regulations, Islamic legal literature, journals, books, and positive legal doctrine. The results of the study indicate that there is synchronization and conflict between Islamic legal norms and positive law in terms of regulations in terms of the substance of the law, however, law enforcement against the use of sound horeg has not been running optimally, which is influenced by cultural and social factors of society. This study provides recommendations so that the integration of both can be carried out harmoniously for the sake of creating social order and protecting people's rights without ignoring religious values ??and individual interests. By providing recommendations for research that changes to the offense in Article 503 of the Criminal Code must be made. The empirical juridical approach has proven effective in understanding the complexity of law application in a dynamic social context